Formulation and Process Optimization of Blondo Separator, Oil,Water and Filtration in Virgin Coconut Oil (VCO) Processing - Supriono, Supriono; Paurru, Shinta Sisilia; Ariusmiati, Ariusmiati; Bary, M. Atta (Sebatik, 2025)
Virgin Coconut Oil (VCO) is a type of pure coconut oil produced without high-temperature heating or the use of chemicals. One crucial stage in VCO production is the separation and filtration of oil, water, and sediment. This research aims to design and evaluate an efficient separator and filter device for small to medium-scale VCO production. The machine applies gravitational and simple centrifugal forces, equipped with a multistage filter system using nylon cloth and filter paper. The results showed that the device achieved 92–95% separation efficiency within 25 minutes per 5 liters of raw material, with a final moisture content of 0.08%. This design can enhance productivity and maintain oil quality, making it suitable for household and small-scale industries.